2008
DOI: 10.1158/1078-0432.ccr-07-4552
|View full text |Cite
|
Sign up to set email alerts
|

Association of p16 Homozygous Deletions with Clinicopathologic Characteristics and EGFR/KRAS/p53 Mutations in Lung Adenocarcinoma

Abstract: Purpose:Thep16 geneis frequentlyinactivatedinlungadenocarcinoma.Inparticular,homozygous deletions (HD)havebeenfrequentlydetectedincelllines; however, their frequencyandspecificityis not well-established in primary tumors.The purpose of this study was to elucidate the prevalence and the timing for the occurrence of p16 HDs inlung adenocarcinoma progression in vivo. Experimental Design: Multiple ligation-dependent probe amplification was used for the detection of p16 HDs in 28 primary small-sized lung adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Therefore, 13q13 alterations were suggested to contribute to the formation of noninvasive tumors irrespective of EGFR/KRAS mutation. We recently reported that p16 homozygous deletions also occur with similar frequencies (f25%) in noninvasive and invasive tumors, in replacement and nonreplacement growth types, and among three groups according to the status of EGFR/KRAS mutations (8). The p16 gene is located on chromosome 9p, which was a hotspot/critical region of AI in both noninvasive and invasive tumors.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, 13q13 alterations were suggested to contribute to the formation of noninvasive tumors irrespective of EGFR/KRAS mutation. We recently reported that p16 homozygous deletions also occur with similar frequencies (f25%) in noninvasive and invasive tumors, in replacement and nonreplacement growth types, and among three groups according to the status of EGFR/KRAS mutations (8). The p16 gene is located on chromosome 9p, which was a hotspot/critical region of AI in both noninvasive and invasive tumors.…”
Section: Resultsmentioning
confidence: 96%
“…The status of EGFR/ KRAS/TP53 mutations in 30 cases was previously reported (6,8). Fortytwo cases were newly analyzed in this study for mutations in exons 18 to 21 of the EGFR gene, in exons 1 to 2 of the KRAS gene, and in exons 4 to 8 of the TP53 gene by genomic PCR and direct sequencing as described previously (6).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations